Candida auris: a bibliometric analysis of the first ten years of research (2009-2018) (2020)
Candida auris (C. auris) is an emerging multidrug resistant fungus considered as the cause of several nosocomial infections of bad prognosis. This study presents a bibliometric analysis of global scientific research on C. auris since it was isolated first in 2009. A systematic search was conducted in Scopus databases in the period of 2009–2018 and a total of 227 indexed documents were retrieved. A sharp increase in the number of studies related to drug and multidrug resistance of C. auris during 2016–2018 was observed, coinciding with an increase in the number of first-case and outbreak reports worldwide. The leading countries based on the number of publications were United States, India, and the United Kingdom. Nevertheless, Netherlands ranked first when (i) ratio between the number of citations and number of publications, (ii) ratio between the number of publications and gross domestic product (GDP), and (iii) ratio between the number of citations and GDP were used as indicators of productivity. Despite the recent emergence of the topic since the first-case report in 2009, recent research efforts have allowed identifying Ibrexafungerp (SCY-078) and Rezafungin (CD101) as possible candidates for facing the actual antifungal resistance of C. auris.